KEIKUTSERTAAN PERANCANG PERUNDANG-UNDANGAN DALAM PEMBENTUKAN PERATURAN DAERAH - Iswahyudi, Fauzi (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
The formation of regional regulation is manifestation of regionl autonomy as mandated Constituion of the Republic of Indonesia to create good regional regulation by participating of legislation designer. Designer of regulation is functional position that has task in design of regulation and arrangement other law instrument. Participating of regulation designer in creating regional regulation wished to minimize problematic regional regulation in application.